Carotid Bifurcation Geometry and Atherosclerosis. (October 2017) - Spanos, Konstantinos; Petrocheilou, Glykeria; Karathanos, Christos; Labropoulos, Nicos; Mikhailidis, Dimitri; Giannoukas, Athanasios
Hemodynamic changes occurring at the initial segments of the arterial bifurcations appear to play an important role in the development of atherosclerotic plaque. Therefore, arterial geometry might be a potential marker for atherosclerosis. Considerable evidence suggests that geometry can influence local hemodynamics at the carotid bifurcation contributing to the development of atheroma. Bifurcation angle, differences in the area ratios including the flare, proximal curvature, sinus bulb width, and tortuosity of the internal or external carotid artery have been listed as potential contributory elements. These morphometric details have been studied not only in postmortem examination but also with the help of imaging modalities such as ultrasound, digital subtraction angiography, computed tomography angiography, and the assistance of computational models and magnetic resonance angiography. The establishment of certain anatomical and geometrical details in addition to traditional risk factors may help in the identification of patients at high risk of developing carotid artery disease. We reviewed the literature to highlight the evidence on the importance of various geometrical details in the development of carotid atheroma and to suggest areas of future research.